2021
DOI: 10.1007/s13337-021-00708-0
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and associated factors of COVID-19 vaccine acceptance among health professionals in Debre Tabor Comprehensive Specialized Hospital, North Central Ethiopia; 2021: cross-sectional study

Abstract: Control of coronavirus disease through vaccination is not merely dependent on vaccine efficacy and safety. Professional and general public acceptance is vital for the successful control of the virus. This study aimed (1) to assess health professionals' attitude towards COVID-19 vaccine acceptance; (2) to identify factors associated with health professional’s attitude towards COVID-19 vaccine acceptance. An Institutional based cross-sectional study was conducted on health professionals working at Debre Tabor Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
57
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 27 publications
10
57
2
1
Order By: Relevance
“…The Ethiopian study also found higher acceptability of a COVID-19 vaccine among physicians, as well as among older HCWs. The majority of HCWs (57%) in the study did not believe that COVID-19 vaccines worked, 62% did not believe that COVID-19 vaccines were safe, and 68% did not trust information on COVID-19 provided by the government [4].…”
Section: Introductionmentioning
confidence: 95%
“…The Ethiopian study also found higher acceptability of a COVID-19 vaccine among physicians, as well as among older HCWs. The majority of HCWs (57%) in the study did not believe that COVID-19 vaccines worked, 62% did not believe that COVID-19 vaccines were safe, and 68% did not trust information on COVID-19 provided by the government [4].…”
Section: Introductionmentioning
confidence: 95%
“…14 Besides this, people's myths and misconceptions about the vaccine, lack of trust in vaccines, unavailability of vaccine, poor knowledge about vaccine, and vaccine hesitancy are some factors that affect the low uptake of COVID-19 vaccine. 15,16 Currently, in Ethiopia, not only new cases but also death rates are rapidly increasing. Therefore, understanding HIV-positive patients' intention to receive COVID-19 vaccine is one of the pillars to lowering the transmission of this pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with the attitude towards COVID-19 vaccine among HCWs were age [56,58,59,64,65,67], gender [59,64,67], race [67], work experience [64], home location [67], having no fear of injections [64], being a non-smoker [64], profession [56,65], presence of chronic illnesses [59], Allergy [59], con dence in pharmaceutical companies [55], con dence in the management of the epidemic [55], history of taking in uenza vaccine [58], vaccine recommendation [58,60], perceived risk of new vaccines [58], perceived utility of vaccine [58], receiving a seasonal u vaccination in the last 5 years [60], working in a private hospital [60], a high perceived pandemic risk index [50], low vaccine harm index [50], high pro-socialness index [50], using Facebook as main information source about antiSARS-CoV-2 vaccination [65], being in close contact with a high-risk group [65], having undertaken seasonal u vaccine during the 2019-2020 season [65], role within the hospital [67], knowledge about the virus [67], con dence in and expectations about personal protective equipment and behaviors [67].…”
Section: Search Resultsmentioning
confidence: 99%